An ETHYLENE INSENSITIVE3-LIKE1 Protein Directly Targets the GEG Promoter and Mediates Ethylene-Induced Ray Petal Elongation in Gerbera hybrida - Huang, Gan; Han, Meixiang; Jian, Lin; Chen, Yanbo; Sun, Shulan; Wang, Xiaojing; Wang, Yaqin (Frontiers in Plant Science, 2020)
Petal morphogenesis has a profound influence on the quality of ornamental flowers. Most current research on petal development focuses on the early developmental stage, and little is known about the late developmental stage. Previously, it was reported that the GEG gene (a gerbera homolog of the gibberellin - stimulated transcript 1 [GAST1] from tomato) negatively regulates ray petal growth during the late stage of development by inhibiting longitudinal cell expansion. To explore the molecular mechanisms of the role of GEG in petal growth inhibition, an ethylene insensitive 3-like 1 (EIL1) protein was identified from the G. hybrida cDNA library approach with yeast one-hybrid screening. The direct binding between GhEIL1 and the GEG promoter was confirmed by electrophoretic mobility shift assay and dual-luciferase assay. The expression profiles of GhEIL1 and GEG were consistent during petal development. The transient transformation assay suggested that GhEIL1 regulates GEG expression and may involve in the inhibition of ray petal elongation and cell elongation. To study the effect of ethylene on ray petal growth, a hormone treatment assay was performed in detached ray petals. The results showed that petal elongation was limited and promoted by ACC and 1-MCP, respectively, and the expression of GhEIL1 and GEG was regulated and coordinated during this process. Taken together, our research suggests that GhEIL1 forms part of the ethylene signaling pathway and activates GEG to regulate ray petal growth during the late developmental stage in G. hybrida.